Eine andere Geschichte der spanischen Literatur Von Cervantes bis zur Gegenwart - Ingenschay, Dieter (De Gruyter, 2022)
This first German-language portrayal of Spanish literature in the digital age offers interpretations that go "against the grain." It makes no claims to academic completeness but is about the transgressive potential of Iberian authors from Cervantes to the present. Special, especially consequential texts are placed within the context of social history (e.g., of the autonomous regions) and are also discussed from a feminist and queer perspective.